PENGARUH KADAR STIMULAN JERUK NIPIS TERHADAP PRODUKSI GETAH PINUS DI DESA NAMO, KABUPATEN SIGI, SULAWESI TENGAH - Hidayat, Rahmat; Hapid, Abdul; Mutmainnah, Mutmainnah (Jurnal Warta Rimba, 2019)
Non-wood forest products (NTFPs) have recently been seen as increasingly important after the productivity of wood from natural forests has declined. Utilization of NTFPs can produce high-value products and be able to contribute to the country's foreign exchange, for example from pine resin products that are processed into Gondorukem derivatives. Determination of the way of tapping pine sap certainly will not be separated from the consideration. From an economic perspective, the consideration is that it is efficient and effective so that it can provide optimal benefits. While in terms of ecology, the consideration is that it does not cause significant damage to the tapped tree. To find alternative ingredients or stimulants that are safe, easy to obtain and able to increase pine resin production, a study was carried out on the effect of lime stimulants in increasing the production of sap in Namo Village. This research was conducted in April to June 2016. This study used a Completely Randomized Design (CRD) with 3 treatments namely 0% stimulant, 25% stimulant, and 50% stimulant. From the results of the study obtained the lowest sap production in the control (without stimulants) of 28.23 gr / tree / 3 days and the highest at 50% stimulant concentration of 70.16 gr / tree / 3 days. Based on LSD test results, it can be seen that the use of lime stimulant with a concentration of 50% has a significantly different effect with a 25% stimulant concentration and control. The concentration of lime stimulant 25% was not significantly different from the control.Keywords: Stimulant Levels, Lime, Production, Pine Gum.